Efficacy of dupilumab in the treatment of severe vulvar pruritus associated with lichen sclerosus et atrophicus: a case report - Du, Na; Mao, Qiuyu; Yang, Jingyi; Zhang, Yiwen; Lyu, Xinyan; Li, Yueyue; Min, Wei; Xu, Jing (Frontiers in Medicine, 2024)
Lichen sclerosus et atrophicus (LSA) is a chronic inflammatory skin lesion with an undefined cause. It is more commonly found in the genital area, particularly in adolescents, premenopausal women and postmenopausal women. LSA is difficult to treat and often recurs. The primary treatment for LSA involves the administration of potent topical corticosteroids. Dupilumab is increasingly being used for the treatment of itching in non-atopic dermatitis patients but there are few reports on its use for the treatment of LSA. Here, we present a case of LSA in a 61-year-old woman with extensive vulvar itching. Over four months of dupilumab therapy, significant therapeutic effects were observed, including vulvar skin thinning and pruritus relief without adverse reactions.